Claude Cahun Je me vois done je suis pour imaginer que je suis autre... - Roque, Renato (Revelar: Revista de Estudos da Fotografia e Imagem, 2019)
Portrait and self-portrait played and still play a relevant role in photography's history. In fact, portrait was the most important field for the affirmation of photography in the 19th century. Photography not only took control of most of the territory, which was a previous possession of painting, but, thanks to its characteristics, was capable of getting into new territories, in terms of representati on, registration and memory. Claude Cahun, a multifaceted artist from the first half of the 2oth century, whose literary and photographic work was forgotten and has been rediscovered recently, used self-portrait as a mediation process between her and the world, between her and her other self, whom she pursued all her life, a self free from social and cultural pressures, with a strategy which we will try to define as anti-narcissistic, in an obsessive search for her true identity. Photography as a quest for truth and liberty. In our essay we go through Cahun's life and work, trying to discover and discuss its revolutionary and innovator content, focusing on one ofCahun's best known self-portraits.